Determining the importance of the criteria of traffic accessibility using fuzzy AHP and rough AHP method - Stanković, Milan; Gladović, Pavle; Popović, Vladimir (Decision Making: Applications in Management and Engineering, 2019)
When defining criteria that have an influence on traffic accessibility, it is necessary to take into account the specificity of a concrete urban unit. A large number of authors base own research on a small number of traffic access criteria using one of the decision-making methods. The methods on which research can be based are multi-criteria decision-making in combination with fuzzy logic and rough numbers that give relevant results and are widely applied in all fields of science today. Thanks to these methods, for problems where is a large number of solutions in which certain criteria are formed, a valid solution can be reached. When using these methods, it is necessary to emphasize that there is a certain degree of subjectivity of the decision maker, but this can be minimized using fuzzy or rough numbers. The aim of this paper is to compare the significance of particular criteria using the Fuzzy AHP method and the Rough AHP method, which would show differences in the values of weight significance criteria and their ranking.